2013
DOI: 10.1111/gtc.12120
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast IQGAP maintains F‐actin‐independent localization of myosin‐II in the contractile ring

Abstract: During cytokinesis in many eukaryotic cells, myosin-II concentrates at the equatorial cortex with actin filaments (F-actin) and is supposed to generate forces to divide the cell into two, which is called the contractile ring (CR) hypothesis. Several lines of evidence indicate that the myosin-II is recruited independently of F-actin and interacts specifically with the equatorial F-actin. Molecular details of these mechanisms are still unknown. We used the fission yeast Schizosaccharomyces pombe to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…We recently reported that several components of the contractile ring of the fission yeast S. pombe, including Myo2, can localize to this structure through both F-actin-dependent and -independent mechanisms, even after the completion of ring assembly, such that when F-actin is lost a fraction of the component remains at the cortical ring (Takaine et al, 2014a). Consistent with our previous findings, we found that mYFP-Myo2 colocalized with F-actin in the medial region as a node structure at early anaphase and as a ring at late anaphase (Fig.…”
Section: Myo3 Localizes To the Contractile Ring By Solely Depending Omentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that several components of the contractile ring of the fission yeast S. pombe, including Myo2, can localize to this structure through both F-actin-dependent and -independent mechanisms, even after the completion of ring assembly, such that when F-actin is lost a fraction of the component remains at the cortical ring (Takaine et al, 2014a). Consistent with our previous findings, we found that mYFP-Myo2 colocalized with F-actin in the medial region as a node structure at early anaphase and as a ring at late anaphase (Fig.…”
Section: Myo3 Localizes To the Contractile Ring By Solely Depending Omentioning
confidence: 99%
“…A 3mYFP-hphMX6 module flanked by homologous sequences (400-500 bp) was amplified using MTP19 (Takaine et al, 2014a) as a template for this purpose. The DNA fragment was transformed into the wt strain MTY10, and transformants were selected for hygromycin resistance.…”
Section: Yeast Strains and Genetic Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…IQGAP1 is an integral component of the yeast actinomyosin contractile ring and is essential for yeast cytokinesis. [22][23][24][25][26][27][28][29][30][31] In the budding yeast S. cerevisiae, Iqg1 co-localizes with filamentous actin and Myo1p, a myosin II homolog, at the mother-bud junction after the initiation of anaphase. 24,25 Here, it regulates formation of the contractile ring, as its overexpression results in it premature formation, 24 whereas its depletion prevents accumulation of actin in the cytokinetic ring.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Rng2 bundles actin filaments 29 and is essential for maintaining myosin-II at the contractile ring. 30 In mammalian cells there are 3 IQGAP proteins, IQGAP1, -2 and -3 among which IQGAP1 and -3 have been linked to cytokinesis. In mouse embryos treated with toxin B, which inhibits Cdc42, the IQGAP upstream GTPase, IQGAP1 localization is disrupted, the actin cytoskeleton is rearranged and cytokinesis is inhibited.…”
Section: Introductionmentioning
confidence: 99%